Nutrient composition of premixed and packaged complementary foods for sale in low‐ and middle‐income countries: Lack of standards threatens infant growth. Issue 4 (22nd December 2016) - Masters, William A.; Nene, Marc D.; Bell, Winnie
Abstract: Premixed flours for infant porridge are increasingly produced and sold in developing countries to complement continued breastfeeding. Such complementary food (CF) products have known efficacy against malnutrition in children from 6 to 24 months of age, but ingredient ratios and production processes may vary. This study provides the first systematic measurement of their actual nutrient composition. We purchased samples of 108 premixed CF products in 22 low‐ and middle‐income countries, and commissioned blind laboratory measurement of each product's macronutrients and micronutrients. We compared measured contents to nutrient claims on their packaging and to CF standards from the Codex Alimentarius, the Super Cereal Plus product used in nutrition assistance programs, and the Lutter and Dewey (2003) recommendations, as well as our own modeled nutrient requirements for a healthy breastfed child. Actual densities are significantly different from nutrient claims for protein ( p = .013) and fat ( p = .000). Only 15% of samples met two of the three benchmarks for fat, 32% met the most stringent protein standard, while only 22% met them for iron, and 21% for zinc. The median healthy child consuming breast milk plus enough of these solid foods to meet energy needs would experience deficits of zinc at 6 months, iron at 6 and 9 months, and dietary fat from 12 months of age. In summary, premixed CF products can provide adequate nutrient density but usually do not, revealing the need and opportunity for independent monitoring and quality assurance to help grain millers making premixed foods maintain uniform ingredient ratios and production practices.